The Prevalence of Vitamin D Deficiency, Its Predisposing Factors and Association with 24-hour Urine Metabolites Among Iranian Kidney Stone Formers (Iranian Journal of Kidney Diseases, 2021)
Introduction. To study the prevalence of vitamin D deficiency in kidney stone formers and its predisposing factors and to assess the relationship between serum 25-Hydroxyvitamin D and urine metabolites. Methods. Kidney stone formers were selected from the records of the kidney stone prevention clinic in Labbafinejad hospital, Tehran, Iran. Vitamin D deficiency was defined as 25-Hydroxyvitamin D < 20 ng/mL. The association between vitamin D deficiency and predisposing factors, serum, and urine metabolites was evaluated. Results. In 1005 patients (66.4% men and 33.6% women), the prevalence of vitamin D deficiency was 44.8%. Vitamin D deficiency was more prevalent in patients under 50 years (P < .001) and patients with hyperparathyroidism (P < .05). The lowest prevalence of hyperparathyroidism was in the 25-Hydroxyvitamin D range of 40 to 49.9 ng/mL, followed by the range of 30 to 39.9 and 20 to 29.9 ng/mL. Patients with vitamin D deficiency had lower serum creatinine (P < .02), lower 24-hour urine calcium (P < .01), and lower 24-hour urine oxalate (P < .05). Conclusion. Iranian kidney stone formers have a relatively high prevalence of vitamin D deficiency. Our population seems to have different predisposing factors for vitamin D deficiency, i.e., higher prevalence among younger patients and no association between obesity and gender with vitamin D status. According to the parathyroid hormone, the favorable serum 25-Hydroxyvitamin D level was 20 to 49.9 ng/mL in our kidney stone formers.DOI: 10.52547/ijkd.5957